Confronting Post-Traumatic Stress Disorder: Towards the Integration of Psychotherapy and Educational Support - Taha Taha; Mohammad Hussein; Raad Amir; Habib Al Bayati (مجلة ابحاث كلية التربية الاساسية, 2024)
This research clarifies the meaning of the phrase post-traumatic stress disorder (PTSD) and the critical importance of understanding this psychological disorder that may result from exposure to a variety of painful and traumatic events, by analyzing the psychological and physical effects of post-traumatic stress disorder (PTSD), as this research sheds light There is a need for multiple treatment methods, including psychological and pharmacological treatment. In addition, the research highlights the importance of psychological and educational support in educational institutions to help individuals affected by the conditions they experienced after trauma, emphasizing the role of psychotherapy in achieving positive functional changes in the brain that help overcome symptoms.